The Effects of Aloe Vera Gel Addition on the Effectiveness of Sunscreen Lotion - Tri Yuni Hendrawati; Hana Ambarwati; Ratri Ariatmi Nugrahani; Susanty Susanty; Ummul Habibah Hasyim (Jurnal Rekayasa Proses, 2020)
especially in cosmetics. The aloe plant that is cultivated in Indonesia to supply this industry is Aloe chinensis Baker. This research is to determine the effects of Aloe vera gel extract on the effectiveness of sunscreen lotion. The steps taken included Aloe vera gel extraction, flavonoid absorption test, sun protection factor (SPF) value measurement, pH test, viscosity test, homogeneity test, and organoleptic evaluation. The extract was added to the base sunscreen formulation at five different concentrations. UV-Vis spectrophotometry at 290 – 320 nm was performed on the preparations to determine their SPF values. The highest SPF value of 10.21 was found in the preparation containing 20% Aloe vera gel extract. This value falls within the national industrial standard for sunscreen SPF value range of 2 – 60. The research showed that a higher concentration of Aloe vera gel extract increased the pH, with the most elevated pH at 7.0 for the preparation containing 20% Aloe gel vera extract. This value also falls within the national pH standard for sunscreen of 4.5 – 8.0. The higher concentration of Aloe vera gel extract also increased the dispersive amount of the sunscreen preparation, with the highest value of 5 cm resulting from 20% Aloe vera gel extract addition. This research showed that the increased addition of Aloe vera gel extract resulted in higher SPF value. A B S T R A KLidah buaya adalah salah satu tanaman obat yang banyak digunakan dalam industri farmasi, terutama di bidang kosmetik. Tanaman lidah buaya yang dibudidayakan di Indonesia untuk memasok kebutuhan  industri adalah Aloe jenis Chinensis Baker. Penelitian ini bertujuan untuk mengetahui pengaruh ekstrak gel lidah buaya terhadap efektivitas lotion tabir surya. Langkah-langkah yang diambil adalah ekstraksi gel lidah buaya, uji serapan flavonoid, pengukuran nilai sun protection factor (SPF), uji pH, uji viskositas, uji homogenitas, dan evaluasi organoleptik. Ekstrak ditambahkan ke formulasi tabir surya dasar pada lima konsentrasi yang berbeda. Spektrofotometri UV-Vis pada panjang gelombang 290-320 nm dilakukan pada persiapan untuk menentukan nilai SPF tabir surya aloe vera. Nilai SPF tertinggi sebesar 10,21 ditemukan dalam sediaan yang mengandung 20% ekstrak gel lidah buaya. Nilai ini termasuk dalam Standar Industri Nasional (SNI) untuk kisaran nilai SPF tabir surya 2-60. Penelitian menunjukkan bahwa konsentrasi yang lebih tinggi dari ekstrak gel lidah buaya meningkatkan pH, dengan pH tertinggi pada 7,0 untuk preparasi yang mengandung 20% ekstrak lidah buaya. Nilai ini juga berada  kisaran standar pH nasional untuk tabir surya 4,5-8,0. Semakin tinggi konsentrasi ekstrak gel Aloe vera juga meningkatkan nilai dispersif sediaan tabir surya, dengan nilai tertinggi 5 cm yang dihasilkan dari penambahan 20% ekstrak lidah buaya. Penelitian ini menunjukkan bahwa penambahan ekstrak gel lidah buaya menghasilkan nilai SPF yang lebih tinggi.